2017
DOI: 10.1186/s40478-017-0422-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic stability of oligodendrogliomas at recurrence

Abstract: Among diffuse gliomas, oligodendrogliomas show relatively better prognosis, respond well to radiotherapy and chemotherapy, and seldom progress to very aggressive tumors. To elucidate the genetic and epigenetic background for such behavior and tumor evolution during tumor relapse, we comparatively analyzed 12 pairs of primary and recurrent oligodendrogliomas with 1p/19q-codeletion. Initial treatment for these patients was mostly chemotherapy alone. Temozolomide was used for 3, and procarbazine, nimustine and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 36 publications
(57 reference statements)
4
52
0
Order By: Relevance
“…11 Whole exome sequencing identified FUBP1 on 1p31.1 and CIC on 19q13.2 as the most frequently mutated genes on 1p and 19q in oligodendrogliomas, but the mutation rates remain 50%-60% at most, 12 and meticulous studies on mutational landscape have shown that mutations of those two genes can be heterogeneous within a tumor, indicating mutations of those genes are later events following the translocation. 13,14 In Although the 19-loss-only astrocytomas appear to constitute only <10% of lower grade astrocytomas, and hence pose limitations to our study, the validation study on the independent TCGA dataset was in line with our notion.…”
Section: Validation Analysis On Tcga Datasetsupporting
confidence: 70%
“…11 Whole exome sequencing identified FUBP1 on 1p31.1 and CIC on 19q13.2 as the most frequently mutated genes on 1p and 19q in oligodendrogliomas, but the mutation rates remain 50%-60% at most, 12 and meticulous studies on mutational landscape have shown that mutations of those two genes can be heterogeneous within a tumor, indicating mutations of those genes are later events following the translocation. 13,14 In Although the 19-loss-only astrocytomas appear to constitute only <10% of lower grade astrocytomas, and hence pose limitations to our study, the validation study on the independent TCGA dataset was in line with our notion.…”
Section: Validation Analysis On Tcga Datasetsupporting
confidence: 70%
“…More recent studies have identified distinct CIC missense mutations within a single tumor, suggesting that selective pressure to inactivate CIC function causes several subclones to acquire distinct mutations independently, thereby contributing to intratumoral heterogeneity [56]. These CIC mutations are not always maintained in recurrent oligodendrogliomas, adding further support to the concept that some of these mutations may be subclonal secondary events [57]. Finally, the presence of mutated CIC alleles correlates with a more aggressive phenotype when compared to tumors that only harbor the 1p/19q co-deletion, indicating that Embryonic or perinatal lethality with incomplete penetrance and hyperproliferation of neural stem cells in the SVZ [42] complete inactivation of CIC function actively contributes to tumor progression [58].…”
Section: Cic Is a Tumor Suppressormentioning
confidence: 94%
“…Through profiling 4 to 5 regions of primary tumors from 11 patients with HC, Lin and colleagues determined that, on average, 39% of somatic mutations varied across the spatial samples studied from each patient’s tumor [27]. This is similar to the 36% seen across 3 to 4 samplings each from 13 patients with esophageal squamous cell carcinoma (ESCC) [10] and 43% seen in 4 patients with oligodendroglioma [28]. However, this difference in spatial somatic mutation varied widely per patient, ranging from 5–92% in HC, 8–61% in ESCC, and 10–64% in oligodendroglioma, demonstrating the unique evolutionary trajectory inherent to different cancer types and to each individual patient.…”
Section: Tumor Heterogeneity Exists At Multiple -Omic Levelsmentioning
confidence: 98%
“…This study took findings one step further, however, by identifying recurrent molecular alterations seen in relapse, including reversion mutations in BRCA1 and BRCA2 and translocation of the ABCB1 gene such that it becomes fused to a strong promoter. Interestingly, Aihara and colleagues employed exome sequencing of 12 paired primary and recurrent oligodendrogliomas resected from patients as part of routine clinical care to demonstrate that approximately one-third of mutations from the primary tumor are retained in the recurrent tumor [28]. Thus, despite limited access to sequential samples, several groups identified temporal heterogeneity in various cancers as evidenced by changes in subclonal dynamics and in overall mutational burden over time.…”
Section: Tumor Heterogeneity Exists At Multiple -Omic Levelsmentioning
confidence: 99%